2007
DOI: 10.1080/00365540701466249
|View full text |Cite
|
Sign up to set email alerts
|

A case of meningoencephalitis associated with G1P[8] rotavirus infection in a Japanese child

Abstract: We report the case of a 2-y, 11-month-old boy with G1P[8] rotavirus infection accompanied by acute meningoencephalitis. Substitutions in both the VP4 and VP7 genes were found in the identified strain. A commonly circulating G1P[8] rotavirus with such mutations might be associated with the pathogenesis of CNS complications, including meningoencephalitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Typically, rotavirus gastroenteritis begins with a mild‐to‐moderate fever and vomiting, followed by the onset of frequent watery stools. While the clinical complaints are generally intestinal, there is evidence of disease outside the gastrointestinal tract, including elevated liver transaminases, 1 benign infantile convulsions, 2 severe central nervous system disease, 3 and necrotizing enterocolitis (NEC) 4 . In this paper, we report an infant with severe hematemesis and melena, caused by an acute duodenal ulcer associated with rotavirus infection.…”
mentioning
confidence: 94%
“…Typically, rotavirus gastroenteritis begins with a mild‐to‐moderate fever and vomiting, followed by the onset of frequent watery stools. While the clinical complaints are generally intestinal, there is evidence of disease outside the gastrointestinal tract, including elevated liver transaminases, 1 benign infantile convulsions, 2 severe central nervous system disease, 3 and necrotizing enterocolitis (NEC) 4 . In this paper, we report an infant with severe hematemesis and melena, caused by an acute duodenal ulcer associated with rotavirus infection.…”
mentioning
confidence: 94%
“…[7] Rotavirus infections rarely cause other complication and for a well-managed child, the prognosis is excellent. [8,9] There are reports of complication involving the central nervous system (CNS) where rotavirus was detected in the cerebro-spinal fluid (CSF) in cases of encephalitis and meningitis [10][11][12] and recent studies have confirmed that rotavirus infection is not always confined to gut, but can cause viremia. [13] Hence, this study was undertaken to find out characterization of rotavirus in stool sample which was paired with other sample like serum, urine and saliva in children below 5 years hospitalized for acute diarrhea in order to study the extent of viremia.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the literature revealed 794 publications, 83 of which were included in this systematic review (Figure 1). Out of these, 68 permitted a detailed analysis of cases 4–8,11,17–78 while 15 publications, dealing with CwG and rotavirus infection, only reported prevalence and therefore did not allow a detailed analysis 10,48,79–91 . Although these latter 15 publications were not included in the systematic analysis, they were used to calculate the prevalence of CwG in rotavirus infection or the prevalence of rotavirus infection in patients with CwG (Figure 1).…”
Section: Resultsmentioning
confidence: 99%